Effects of tetraalkylammonium salts on Brdicka and presodium currénts of bovine-serum albumin. - Kolthoff, I M (1975)
Tetraethyl-, tetrapropyl-, and tetrabutylammonium ions are capillary-active on the interface water-mercury. In the adsorbed state they increase Brdicka and presodium currents. These currents drop sharply at potentials where tetrabutylammonium ions are desorbed, these potentials being -1.60, -1.66, -1.72, and -1.79 V versus the saturated calomel electrode (SCE) at tetrabutyla-mmonium concentrations of 0.1, 0.25, 1, and 5 mM, respectively. Indications are that tetraethylammonium ions at a concentration of 50 mM are desorbed at a potential of the order of -1.9 V (versus SCE). The increase of Brdicka currents is attributed--at least in part--to a decrease in the rate of electroreduction of cobalt(II). In the desorbed state the effect--if any--of tetrabutylammonium ions on Brdicka and presodium currents is very small. Tetrabutylammonium ions also greatly increase Brdicka currents observed with cysteine, the effect disappearing after these ions attain their desorption potential. The effect of tetraphenylarsonium on Brdicka currents is very similar to that of tetrabutylammonium, while that of diphenylguanidine is similar to that of tetraethylammonium ions.